A Study of the ST Changes in the aVR Lead on 12-Lead ECG to Identify Infarct - Related Artery (IRA) in Patients With Acute Inferior Wall Myocardial Infarction - Mahaseth, Aditya; Nepal, Bikas; Karki, Biplave; Ghimire, Jeet; Pandey, Naveen; Shah, Prashant; Karki, Prahlad (Nepal Mediciti Medical Journal, 2021)
BACKGROUND: Lead avR is a valuable but mostly ignored lead in clinical electrocardiography. Recently, ST-segment depression in lead aVR during an inferior wall myocardial infarction has been suggested as a predictor of LCX artery involvement. METHODS: This study was a single centre cross sectional observational study done in BPKIHS, Dharan from February 2018 to January 2020. Patients presenting to the OPD or emergency room of BPKIHS diagnosed as acute inferior wall myocardial infarction based on clinical symptoms, ECG and/or Cardiac tropinin I levels, and planned for coronary angiography, meeting the inclusion and exclusion criterias were included. RESULTS: Among 134 cases, male:female ratio was 1.3:1. Overall, 38 patients (28.4%) were found to have aVR depression and 96 patients (71.6%) were without aVR depression. The culprit artery was found to be the right coronary artery in 95 patients (70.9%), the LCx in 39 patients (29.1%). The sensitivity and specificity of ST-segment depression in lead aVR for LCx as the culprit artery were 92.3% and 97.9% respectively. Positive predictive and Negative predictive value for LCx as the culprit arteries were 94.74% and 96.87%. The sensitivity, specificity, positive predictive value and negative predictive value for RCA as the culprit artery were 97.89%, 92.3%, 96.89% and 94.73% respectively. CONCLUSION: Significant ST depression in aVR is associated with a higher specificity and good sensitivity for LCX lesions, the ST changes in this lead should be carefully examined in all patients who are suspected of having inferior wall myocardial infarction.